Differentiation ability of rat‐mesenchymal stem cells from bone marrow and adipose tissue to neurons and glial cells - Ariyani Noviantari; Ratih Rinendyaputri; Ibnu Ariyanto (Indonesian Journal of Biotechnology, 2020)
Mesenchymal stem cells (MSCs) are multipotent cells and can differentiate into neurons and glial cells. In vitro differentiation would be done by the addition of various factors. There remains no comparison for the differentiation of MSCs from rat bone marrow (rBMMSCs) and adipose tissue (rATMSCS) into neurons and glial cells with basic fibroblast growth factor (bFGF), epidermal growth factor (EGF), and brain‐derived neurotrophic factor (BDNF). The aims of this study were to investigate the effect of bFGF, EGF, and BDNF supplementation on the differentiation ability of rBMMSCs and rATMSCs into neurons and glial cells. MSCs were cultured with bFGF and EGF for 4 days and then BDNF was added until day 8. Characterization of MSCs before and after induction was carried out by observing the cell morphology and several cell markers. Flowcytometry analysis was performed for MSCs markers (CD90, CD29) and neurons and glial cell markers (A2B5, Beta‐III‐tubulin, PSAN‐CAM); while MAP‐2, a neuron marker, was analyzed by immunocytochemistry. Induction of both types of MSCs showed MAP‐2‐positive cells, decreased MSCs markers, and in rBMMSCs showed increased neuron markers. The number of neuron marker positive cells in rBMMSCS was higher than rATMSCs. This study showed that the addition of bFGF, EGF, and BDNF to the medium induced rBMMSCs into neurons and glial cells, but the conditions were not optimal for rATMSC as judged by the expression of neural markers (A2B5, Beta‐III‐tubulin, PSAN‐CAM, and MAP‐2).